Activated PI3Kδ syndrome 1 mimicking systemic lupus erythematosus and secondary Sjögren's syndrome-like phenotype without recurrent infections: A case report - Yin, Jing; Ma, Jijun; Xia, Jingyue; Cao, Yang; Li, Chongwei (Frontiers in Pediatrics, 2022)
Activated phosphoinositide 3-kinase-δ syndrome 1 (APDS1) is a combined immunodeficiency caused by a heterozygous gain-of-function mutation in PIK3CD, encoding the p110δ catalytic subunit of phosphoinositide 3-kinase δ (PI3Kδ). APDS1 is characterized by recurrent sinopulmonary infections, leading to airway damage, chronic herpes viremia, lymphoproliferation, and autoimmune and inflammatory diseases. Several cases of systemic lupus erythematosus (SLE) have been reported in APDS1; however, Sjögren's syndrome (SS) or an SS-like phenotype is rarely described in patients with APDS1. In this study, we report a four-year-old girl with APDS1 who did not experience recurrent sinopulmonary infections and chronic viremia but presented with cytopenia, proteinuria, hypocomplementemia, and positive antinuclear antibodies that met the classification criteria for SLE. Additionally, the patient also mimicked a secondary SS-like phenotype based on recurrent parotitis and labial salivary gland biopsy. The patient achieved remission after treatment with sirolimus and immunosuppressive therapy. This case report enriches the clinical phenotype of APDS1 and provides a reference for the diagnosis and therapy of patients with APDS1.